PENGARUH MANAGERIAL ABILITY DAN KARAKTERISTIK PERUSAHAAN TERHADAP PRAKTIK PENGHINDARAN PAJAK - Faza Nisasilmi Nasuha; Sony Devano; Selly Herdianti (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of managerial ability and company characteristics proxied by profitability, leverage, and company size on taxㅤavoidance. The researchㅤpopulation is manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling methodㅤused was purposiveㅤsamplingㅤandㅤobtained 87 observations in the consumer goods sector. Hypothesis testing in this study uses the PanelㅤData regression statistical test with the Fixed Effect Model (FEM) model. Theㅤresults of theㅤanalysis show that partially the managerialㅤability variable and company characteristics proxied by profitability, leverage, and company size haveㅤaㅤnegative effect onㅤthe Effective tax rate (ETR). This means that the higher the profitability, the smaller the ETR. The smaller the ETR indicates the higher the tax avoidance. So managerial ability, profitability, leverage, and company sizeㅤhave aㅤpositive influence on tax avoidance. And simultaneously the variables of managerial ability, profitability, leverage, and companyㅤsizeㅤaffect tax avoidance practices.